CHANGES IN THE RISE OF THE CIVIL POSITION OF YOUNG PEOPLE AND THE CRITERIA FOR ITS ASSESSMENT AND INDEXERS - Jumaev Sarvarbek Soyibjan Ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article will talk about the concept of citizenship, and changes in the rise of the civic position of young people, in particular student youth.